An Analysis Of Students’ Ability to Using Punctuation In Writing Texts of English Education Students in the Fourth Semester at State Islamic University of Sjech M. Djamil Djambek Bukittinggi Academic Year 2021/2022 - Siti Mardiah; Melyan Melani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The purpose of the research was to find out the level of students’ ability about using punctuation marks in writing the text of English Education Students in the Fourth Semester at IAIN Bukittinggi academic year 2021/2022. The design of this research was descriptive quantitative research. The instruments of this research were punctuation tests in writing the text for measuring students’ ability in Using Punctuation in Writing Text. The population of this research was all Students in Fourth Semester at IAIN Bukittinggi Academic Year 2021/2022 which consists of 4 classes. The sample was 32 students taken by simple random sampling technique. The results of the research show that the mean score was 66 and the lowest score was 33 and a higher score was 93 from 67 students’ Fourth Semester at IAIN Bukittinggi academic year 2021/2022. As a result, the researcher used a ranting scale to arrange the level of students’ ability in using Punctuation Marks in Writing Text. The interpretation table showed that the percentage of the students' mean score was 66 with ranting 66%-79%. The finding showed that the level of students’ ability in using Punctuation Marks in Writing Text with a score percentage of 66 was a good category.